PERAN EFIKASI DIRI DAN SCHOOL BELONGINGNESS TERHADAP PERMASALAHAN EMOSI DAN PERILAKU REMAJA - Nur Amanah Ridho Salsabiela; Edilburga Wulan Saptandari (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2025)
This decade, Emotional Behavior Problems (EBP) among teenagers shows a prevalence rate that tends to be high both globally and nationally. Self-efficacy and school ownership are assessed as predictors of EBP, so this research aims to determine the negative role of self-efficacy and school ownership on Emotional Behavioral Problems (EBP) of adolescents who are junior high school (SMP) students. A total of 169 students of SMPN X and SMPN Y in Yogyakarta City were participants in this research. Participants were taken using purposive sampling technique. The instruments used in this research are three scales which include the Strengths and Difficulties Questionnaire (SDQ), General Self-Efficacy (GSE), Psychological Sense of School Membership (PSSM). Multiple linear regression analysis showed that self-efficacy and sense of school belonging simultaneously could not predict EBP. Meanwhile, separate predictor analysis was able to predict EBP. Additional analyzes showed no significant differences in EBP by gender, grade level, or family condition